SEG Technical Program Expanded Abstracts 2016 2016
DOI: 10.1190/segam2016-13865457.1
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear approach of elastic reflection waveform inversion

Abstract: SUMMARYElastic full waveform inversion (EFWI) embodies the original intention of waveform inversion at its inception as it is a better representation of the mostly solid Earth. However, compared with the acoustic P-wave assumption, EFWI for P-and S-wave velocities using multi-component data admitted mixed results. Full waveform inversion (FWI) is a highly nonlinear problem and this nonlinearity only increases under the elastic assumption. Reflection waveform inversion (RWI) can mitigate the nonlinearity by rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…With a least-square optimization to the predicted image, Wu and Alkhalifah (2015) proposed a new optimization problem where the background model and perturbations are inverted simultaneously. Subsequently, Guo and Alkhalifah (2016) brought the concept of RWI to elastic media and developed elastic reflection waveform inversion that aims to invert for the long wavelength components of P-and S-wave velocities. However, the variable density as a potential reflector, with little influence on the propagation of waves, can not be neglected as a perturbation parameter.…”
Section: Introductionmentioning
confidence: 99%
“…With a least-square optimization to the predicted image, Wu and Alkhalifah (2015) proposed a new optimization problem where the background model and perturbations are inverted simultaneously. Subsequently, Guo and Alkhalifah (2016) brought the concept of RWI to elastic media and developed elastic reflection waveform inversion that aims to invert for the long wavelength components of P-and S-wave velocities. However, the variable density as a potential reflector, with little influence on the propagation of waves, can not be neglected as a perturbation parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al (2012) suggested using a reflection waveform inversion (RWI) method, which aim to invert the long-wavelength components of the model by using the reflections predicted by migration/demigration process. Through minimizing misfit function of waveform, the RWI method are developed by several work (Wu and Alkhalifah, 2015;Zhou et al, 2015), and recently extended to elastic case by Guo and Alkhalifah (2016).…”
Section: Introductionmentioning
confidence: 99%